Aboriginal Children's Hurt & Healing (ACHH) Initiative: First Nation community health video (First Peoples Child & Family Review, 2019)
The Aboriginal Children’s Hurt & Healing (ACHH) Initiative is a research initiative aimed at improving Indigenous children’s healthcare experiences. The ACHH Initiative seeks to recognize the pain and hurt experience of Indigenous children and youth by gathering individual stories and artwork to better understand cultural differences for both the emotional and physical pain experience. The ACHH Initiative, in collaboration with several First Nations communities across the Mi’kma’ki and Wolastoqey regions, offered conversation and art sessions to community members. A knowledge sharing video communicating community ideas from this work was developed, with youth identifying emotional pain depicted through artwork. This knowledge represents a profound cultural understanding of pain as something that is experienced on multiple levels - physical, emotional, mental and spiritual. This video was produced by RPM Productions.